KONDISI FISIK SISWA EKSTRAKURIKULER SEPAK BOLA SMAN 1 SEBERUANG - Mathias Vidarius Kase; Ahmad Atiq; Muhammad Fachrurrozi Bafadal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Vo2max is the most important element as the basic foundation of a student. For this reason, this study was conducted to determine the vo2max level, especially in the Physical Condition of the Football Extracurricular Students of SMAN 1 Seberuang, and will be used as initial data to serve as a benchmark for evaluation and development in making exercises, especially on the vo2max element of the Physical Condition of the SMAN 1 Football Extracurricular Students. A bear. This study uses a survey system approach where the data obtained from the results of the tests that have been carried out, with the Multistage Fitness Test (MFT) instrument, were studied with quantitative descriptive methods. The study was piloted on all 33 students of SMAN 1 Seberuang Soccer Extracurricular, consisting of 20 female students and 13 male students. The results showed that the vo2max status of the students of SMAN 1 Seberuang was more dominant in the very poor category with the number of categories being less than 15 students with a vo2max prediction (23-32.4.) Students with a 30-meter sprint test are divided into 3 categories including 14 students with time travel distance (3.19-3.45,) while there are 14 students with travel distance (4.10-4.77) and sufficient category there are 5 students with distance traveled (5.09-5.34.) Based on these results, it can be concluded that there is still a need for improvement in the preparation of the training program to support improvements, especially in increasing vo2max in soccer extracurricular students at SMAN 1 Seberuang.